Boso Rexmax: Characteristics, Social Functions, and Identity of the Kauman Village Community, Ponorogo (A Sociolinguistic Study) - Suyuti, Muhammad Wildan (Jurnal Sastra Indonesia, 2024)
This study examines boso rexmax, a unique reversed language from Kelurahan Kauman, Ponorogo, which developed as a secret language during the colonial era. The research analyzes the linguistic characteristics, social functions, and contemporary dynamics of boso rexmax usage. Using a qualitative descriptive method with an ethnographic approach, this study involved participatory observation, in-depth interviews, and analysis of linguistic artifacts over four months. The results reveal that boso rexmax possesses a complex linguistic structure, incorporating Javanese script and specific reversal rules that vary based on word types. This language is a secret communication tool, a strong identity marker, and a medium for non-formal education. Its active use across various age groups demonstrates its vitality and role in strengthening social cohesion. Boso Rexmax has transformed from a secret language into an integral component of local cultural identity, showcasing the ability of regional languages to adapt and survive in the modern era. This research contributes to a deeper understanding of local language dynamics and their role in preserving cultural identity while providing a foundation for comparative studies and future language preservation efforts.